If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-3x+8x=2(3x+2)-3
We move all terms to the left:
2-3x+8x-(2(3x+2)-3)=0
We add all the numbers together, and all the variables
5x-(2(3x+2)-3)+2=0
We calculate terms in parentheses: -(2(3x+2)-3), so:We get rid of parentheses
2(3x+2)-3
We multiply parentheses
6x+4-3
We add all the numbers together, and all the variables
6x+1
Back to the equation:
-(6x+1)
5x-6x-1+2=0
We add all the numbers together, and all the variables
-1x+1=0
We move all terms containing x to the left, all other terms to the right
-x=-1
x=-1/-1
x=1
| 2^x+2=5 | | 1/2(b+14)=b+12/2 | | 4w/7=-8 | | 2(2x+3)+2-5x=7-2x | | 2x-9=7(x+3) | | -2u=6/7 | | -5w+12w+9=4w=42 | | -5+(z-7)-z=-8 | | 6x-3=6x+4 | | K)x-2/3-12-x/2=5x-36/4-1 | | 2a-3(a+6)=-a-11 | | -c+(9+c)=4 | | 0.6+x=0.8+0.6x | | 2.7q-5.1-2.4q=-0.7q-3.6 | | 8x-3-2(3x+3)=3x-8 | | 3x-2(3x-2)+2=7-4x | | 2(12+x)=2x+23 | | 8x+10+3x+10=180 | | (e+5)×3=18 | | 0.36(0.36)x=-1.8(0.36) | | 3x+2(-3/2x)=4 | | 3x-1+2x=3(2x+2)-8 | | 3x+2(3/2x)=4 | | -.0.2(50)+0.8x=0.3(50+x) | | 14=7(m−95) | | x+1/4=-7/2 | | 2(3x-1)+2x-3=9x-8 | | -30c+3c-7(2-3c)=4(c-5)+3c+27 | | 3(2x-1)-2+3=9x-2x | | |2x-1.8|=-3.6 | | 6a+5=4a+7 | | X^2-8x-9x=5 |